Basic Need Analysis in Practical English Grammar: An Effort on Creating and Empowering Autonomy Learners - Dwi Astuti Wahyu Nurhayati (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
This paper presents the students’ need analysis in Practical English Grammar course. The data were collected through questionnaires and interview by individual or group assessment. It involves 34 Indonesian undergraduate students who were majoring in English, took, join Grammar class and conducted classroom interaction in English teaching and learning process in IAIN Tulungagung, East Java, Indonesia. The data were analyzed using descriptive qualitative approach. The finding revealed some students’ perspectives on Practical English Grammar course (lack of learning media, ineffective teaching strategy, unsupportive class atmosphere, and Grammar as difficult course); some student-considered effective ways to learn Practical English grammar (YouTube, discussion, appropriate learning techniques, progress report, peer assessment, and game); and students’ results on their need analysis in learning Practical English Grammar in form of independent option on: learning media, learning strategy, learning material, and creating own questions and its answers.